2016
DOI: 10.1016/j.pestbp.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide sensitivity of native chloride and sodium channels in a mosquito cell line

Abstract: 2016-11-02T18:49:00

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“… aegypti . ANK , ankyrin-2 [33,35]; aPKC , atypical Protein kinase C [74]; β-SPEC , beta-spectrin [35,74,76]; CAa1 , calcium channel alpha subunit [30,31]; CHL , CHARLATAN [25,26] ; NEDD4 , E3 ubiquitin-protein ligase [37,38]; NVY , NERVY [42–44], PUM , pumilio [27], SYT1 , SYNAPTOTAGMIN-1 [87,90]; VGSC , voltage-gated sodium channel [74]. Dotted line indicates indirect interaction due to shared roles in synaptic function.…”
Section: Discussionmentioning
confidence: 99%
“… aegypti . ANK , ankyrin-2 [33,35]; aPKC , atypical Protein kinase C [74]; β-SPEC , beta-spectrin [35,74,76]; CAa1 , calcium channel alpha subunit [30,31]; CHL , CHARLATAN [25,26] ; NEDD4 , E3 ubiquitin-protein ligase [37,38]; NVY , NERVY [42–44], PUM , pumilio [27], SYT1 , SYNAPTOTAGMIN-1 [87,90]; VGSC , voltage-gated sodium channel [74]. Dotted line indicates indirect interaction due to shared roles in synaptic function.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lindane increased chloride current amplitude. This finding is not only the first report of type 2 pyrethroid inhibition of insect voltage-sensitive chloride channels, but also shows that Sua1B cells express native insect ion channels with potential utility for insecticide screening [ 119 ]. The RML12 cell line derived from Aedes albopictus displays spontaneous electrophysiological activity differentiated with 20-HE.…”
Section: Application Of Insect Cell Lines In Pest Managementmentioning
confidence: 77%
“…There have been a number of studies in which cultured insect cells have been treated with the molting hormone 20‐hydroxy ecdysone (20‐OH E) and which have resulted in a more spindly shape as the cells differentiate into neuron‐like structures with longer processes. In some cases, it appears that voltage‐gated sodium, calcium, potassium or chloride channels have been induced concomitant with the morphological change 37–41 . More recently, it has been shown that 20‐OH E treatment of Aedes RML12 cells led to spontaneous neuroactivity as monitored by multiwell microelectrode array, and that this could be enhanced by treatment with the GABA antagonist gabazine and especially nicotine 42 …”
Section: Lab‐on‐a‐chip or Organ‐on‐a‐chip Technologies For Insecticide Screening Or Mode Of Action Studiesmentioning
confidence: 99%